1999
DOI: 10.1007/s000180050354
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosylation of proteins

Abstract: The transfer of a nitric oxide group to cysteine sulfhydryls on proteins, known as S-nitrosylation, is increasingly becoming recognized as a ubiquitous regulatory reaction comparable to phosphorylation. It represents a form of redox modulation in diverse tissues, including the brain. An increasing number of proteins have been found to undergo S-nitrosylation in vivo. These proteins are called S-nitrosothiols, and may play an important role in many processes ranging from signal transduction, DNA repair, host de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
137
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(140 citation statements)
references
References 50 publications
0
137
0
3
Order By: Relevance
“…Recent studies have also established S-nitrosylation of protein cysteine as a major mechanism of NO regulatory signaling (reviewed in Stamler et al, 1997;Broillet, 1999;Hess et al, 2001). Protein S-nitrosylation is linked to the activity of the different NOS isoforms depending on the cell type (Gow et al, 2002).…”
Section: Protein S-nitrosylationmentioning
confidence: 99%
“…Recent studies have also established S-nitrosylation of protein cysteine as a major mechanism of NO regulatory signaling (reviewed in Stamler et al, 1997;Broillet, 1999;Hess et al, 2001). Protein S-nitrosylation is linked to the activity of the different NOS isoforms depending on the cell type (Gow et al, 2002).…”
Section: Protein S-nitrosylationmentioning
confidence: 99%
“…Due to its redox capacity, NO is able to nitrosate many nucleophilic sites on proteins including amines, aromatic rings, alcohols and thiols. Snitrosylation is the transfer of a NO + equivalent on a free SH group of a protein leading to formation of nitrosothiol (RSNO); this reaction is fully reversible (Broillet 1999). NO can be covalently incorporated into cysteine thiols, tryptophan indols and amines, but studies of free-SH groups by radioactive SH modifying reagents, ultraviolet visible spectrometry and electro spray ionization-mass spectrometry have demonstrated that cysteine residues are rapidly nitrosylated while reactions with other amino acids occur at much slower rates, therefore formation of S-nitrosothiol bond by cysteine thiol nitrosylation is considered most important due to its reactivity under Fig.…”
Section: S-nitrosylationmentioning
confidence: 99%
“…Mechanism of Regulation HRI Activity by NO and CO-The physiological effects of NO are mediated through a number of mechanisms, including (i) S-nitrosylation of proteins (30), (ii) the generation of free radicals and oxidative stress (31), or (iii) the coordination of NO by protein-bound heme (12,32). The only known biological reactivity of CO is as a ligand for proteinbound heme, and CO is neither sulfhydryl-nor redox-active.…”
Section: Effect Of No and Co On Protein Synthesis And Eif2␣mentioning
confidence: 99%